Musyawarah dalam Penyelesaian Sengketa Warisan pada Masyarakat Desa Lon Asan Kecamatan Lembah Selawah Kabupaten Aceh Besar: (Analisis Terhadap Konsep Musyawarah Perspektif Al-Qur’an) - Muhibussailin; Helmi; Afrizal; Lhokweng, Emier (Ameena Journal, 2024)
Lon Asan Village, located in Lembah Selawah Sub-district, Aceh Besar Regency, frequently resolves inheritance disputes through deliberation conducted by village authorities and disputing community members. Many cases have been successfully settled through peaceful means, with mutual consent among the disputing parties. This study aims to explore the inheritance dispute resolution system based on the Qur’an. The research questions are: How is the process of deliberation carried out in resolving inheritance disputes in the community of Lon Asan Village, Lembah Selawah Sub-district, Aceh Besar Regency? And how does the process of deliberation in resolving inheritance disputes align with the Qur'anic perspective? This research is a field study with a descriptive approach. The data sources include both primary and secondary data. Data collection techniques involve observation, interviews, and documentation. The collected data are described descriptively and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that inheritance disputes are resolved through deliberation among disputing parties by applying the principles of mutual consent and justice. From the perspective of the Qur’an, the principle of deliberation in resolving inheritance disputes aligns with several Qur’anic verses, including Surah Ash-Shura (42:38) and Surah An-Nisa’ (4:11). Therefore, the community is encouraged to maintain this system when disputes cannot be resolved directly between the involved parties.